2013
DOI: 10.20882/adicciones.30
|View full text |Cite
|
Sign up to set email alerts
|

Variables predictivas del alta terapéutica entre pacientes con patologia dual grave atendidos en una comunidad terapéutica de drogodependencias con unidad psiquiátrica

Abstract: This study aims to analyze the variables on which depends therapeutic discharge, in patients with a severe dual diagnosis admitted to a professional therapeutic community where their pathology is treated. 325 patients admitted between June 2000 and June 2009 to the therapeutic community. This is a retrospective, cross-sectional study with no control group, based on the detailed analysis of the information collected in a model of semi-structured clinical interview designed in the therapeutic community. The 29.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…[46]. Likewise, a previous study reported a relationship between polysubstance use and a lower percentage of therapeutic discharges in DD patients [47].…”
Section: Discussionmentioning
confidence: 82%
“…[46]. Likewise, a previous study reported a relationship between polysubstance use and a lower percentage of therapeutic discharges in DD patients [47].…”
Section: Discussionmentioning
confidence: 82%
“…With respect to the limitations of this study, it is important to consider several methodological issues. For instance, while the statistical analyses controlled for gender and age, certain variables such as the severity of dependency, the sociodemographic profile of the patients (e.g., educational level), and the presence of comorbid mental disorders could also affect the type of discharge (Madoz‐Gúrpide et al., 2013 ). The inclusion of these variables in the models would probably allow us to achieve greater explanatory capacity.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Substance Use Disorders (SUD) are considered chronic disorders (Fleury et al., 2016 ; Lynch et al., 2021 ) whose treatment usually involves relapse (Sliedrecht et al., 2019 ), with high rates of non‐attendance at appointments (Milward et al., 2014 ) and non‐therapeutic discharge (Madoz‐Gúrpide et al., 2013 ). Thus, this therapeutic course is accompanied by progressive deterioration in the physical, psychological, and social health of patients and their families (Laudet et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tampoco el nivel educativo influye en la efectividad, a diferencia del estudio de El diagnóstico psiquiátrico que presentan los sujetos no influye en los resultados, resultado que contradice el de otros estudios (Farren et al, 2013;Farris, Epstein, McCrady y Hunter-Reel, 2012;Madoz-Gúrpide et al, 2013), aunque también hay revisiones que concluyen, al igual que esta tesis, que el diagnóstico psiquiátrico no influye en los resultados de tratamiento (Baker et al, 2009) y en concreto en la efectividad de la entrevista motivacional (Hunt et al, 2013). No obstante, también hay estudios que encuentran que, dentro de un mismo diagnóstico, los síntomas específicos que presentan los sujetos se relacionan con los resultados del tratamiento (GlasnerEdwards, Mooney, Ang, Hillhouse y Rawson, 2013).…”
Section: 54-aspectos Que Se Relacionan Con La Eficacia De La Tpmb-dunclassified
“…Aunque la sustancia de consumo influye en el nivel de satisfacción con la TPMB-D, no se relaciona con el aumento del nivel de conocimientos ni de la motivación para el cambio, en la línea de estudios que encuentran que la sustancia de consumo no influye en la efectividad de programas de contrato, recuerdo y refuerzo de la continuidad de cuidados (Lash et al, 2013), pero diferenciándose de aquellos que encuentran que la sustancia de consumo influye en la probabilidad de alta terapéutica (Madoz-Gúrpide et al, 2013).…”
Section: 54-aspectos Que Se Relacionan Con La Eficacia De La Tpmb-dunclassified